2018
DOI: 10.2337/dc18-0724
|View full text |Cite
|
Sign up to set email alerts
|

Area Deprivation and Regional Disparities in Treatment and Outcome Quality of 29,284 Pediatric Patients With Type 1 Diabetes in Germany: A Cross-sectional Multicenter DPV Analysis

Abstract: This study analyzed whether area deprivation is associated with disparities in health care of pediatric type 1 diabetes in Germany. RESEARCH DESIGN AND METHODS We selected patients <20 years of age with type 1 diabetes and German residence documented in the "diabetes patient follow-up" (Diabetes-Patienten-Verlaufsdokumentation [DPV]) registry for 2015/2016. Area deprivation was assessed by quintiles of the German Index of Multiple Deprivation (GIMD 2010) at the district level and was assigned to patients. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
4
36
2
3
Order By: Relevance
“…Frequency of pump therapy was lower in patients with DKA. Previous studies found that migration background and lower socioeconomic status (SES) are associated with lower frequency of insulin pump therapy, higher BMI, worse metabolic control, and DKA [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of pump therapy was lower in patients with DKA. Previous studies found that migration background and lower socioeconomic status (SES) are associated with lower frequency of insulin pump therapy, higher BMI, worse metabolic control, and DKA [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Propensity score matching was conducted to elicit a control group of DMP participants who matched characteristics of DMP CAD participants with regard to the class variables "sex", "smoking status", "obesity", "angina pectoris", "arterial occlusive disease", "dyslipidemia", "congestive heart failure", "arterial hypertonia", "New York Heart Association (NYHA) state", enrollment in "DMP COPD", and "DMP type 2 diabetes", "stent in the year before AMI". Further, the continuous variables "age", "German Index of Multiple Deprivation 2010 (GIMD 2010)" on district level [22], "HMG compensations per day", and "length of index hospitalization" at baseline. A 1:1 matching was conducted on the logit of the propensity score using calipers of width equal to 0.2 of the standard deviation of the logit of the propensity score [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be the higher proportion of families with low socioeconomic status in the eastern part of the country [30]; a recent study showed that children and adolescents from families with low soci-oeconomic status in Germany are hospitalized more frequently and longer than other children [31]. Moreover, there is some evidence that a higher regional deprivation in the eastern part of Germany leads to worse diabetes outcomes, and also to increased hospital admissions [10,32].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to gain a comprehensive overview of hospitalization (frequency, causes, length of stay) in children and adolescents with diabetes in Germany using the nationwide DRG data. Taking into account a recent report indicating significant regional disparities in pediatric diabetes care in Germany, in particular between the western and the eastern part of the country [10], we additionally compared hospitalizations between east and west residence.…”
Section: Introductionmentioning
confidence: 99%